THE EFFORTS TO IMPROVE THE LEARNING MOTIVATION BY USING DISCUSSION METHODS IN MATHEMATICS FOR VII GRADE STUDENTS - Diah Trie Wahyuni; Abdul Taram (Universitas Ahmad Dahlan, 2018)
The learning method that is less interesting in the Mathematics subject makes the low studentâ€™s motivation to learn Mathematics. This research aims to improve studentâ€™s motivation in Mathematics subject by using the discussion method for VII grade students â€œAâ€ of Muhammadiyah Pakem Junior High School (SMP Muhammadiyah Pakem) at even semester in Sleman districts academic year 2016/2017. This research is Classroom Action Research (CAR). The subject is the seven grades students